Steinhoff international : of growth and corporate governance - Kodongo, Odongo; Bowen, Amanda; Beswick, Claire (London : Wits Business School, 2024)
On 7 May 2019, Steinhoff International, a global retail group based in Stellenbosch, South Africa, published its delayed Annual Report for 2017. The report detailed the results of the company’s investigation into a tangle of accounting irregularities and governance failures that had led to the delay, and resulted in the resignation of the chief executive officer (CEO) Markus Jooste on 6 December 2017, an 80% plunge in the company’s share price over the following 48 hours and the need to restructure debt of more than €10.4 billion (R166 billion). Since these events, the company had put in place numerous measures to prevent such a failure in the future, but the question remained: how could fraud of such massive proportions have happened in the first place? This case study situates Heather Sonn who accepted the role of chairperson of the supervisory board after Jooste’s resignation, looking back at the events that occurred in early December 2017. The delay in the publication of the 2017 Annual Report, the subsequent resignation of Jooste and the release of the Viceroy Report had exposed the shaky foundations of the Steinhoff Empire. The chairperson position presented Sonn with the rare opportunity to be at the forefront of "uncharted territory as nobody in South Africa had chaired a company of comparable size at the centre of the country’s largest corporate fraud". Moreover, she felt a duty to assist those affected by the crisis saying, "We want to uncover the truth, show the world what has happened, prosecute any wrongdoing and reinstate trust in the company."
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporate governance -- Case studies; Corporations -- Finance -- Case studies; Corporations -- Growth -- Case studies